Non-insulin dependent diabetes mellitus and risk factors: a case control study from Andhra Pradesh - Shruti, P.; Takalkar, Anant A. (International Journal Of Community Medicine And Public Health, 2019)
Background: It is well known that several factors influence the development of non-insulin dependent diabetes mellitus (NIDDM) such as genetic, environmental and life style factors. Obesity is the strongest modifiable risk factor for NIDDM. Cigarette smoking and alcohol consumption may also have important roles, either indirectly through their effects on obesity or directly through physiological factors related to insulin secretion or insulin resistance. The objective of the study was to study the risk factors of non-insulin dependent diabetes mellitus among the patients attending Chalmeda Anand Rao Institute of Medical Sciences Hospital. Methods: It is a hospital-based case-control study for risk factors in NIDDM. The study was conducted at Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar during the period of June 2010 to May 2011 involving 147 cases and controls each. Data collected and analyzed using SPSS 14 version. Results: 21.59% of the male cases were in the age group of 46-50 years and 20.97% female cases from 56-60 yrs age. 42% cases and 12% controls had history of diabetes mellitus in one parent. 34% cases and 4.67% controls had history of diabetes mellitus in both the parents. Current smokers (odds ratio-4.24, 95% CI 2.02-9.15) and ex-smokers (odds ratio-1.31, 95% CI 0.65-2.68) exhibited an increased risk of NIDDM. Ex-drinking but not current-drinking was statistically significantly associated with the risk of NIDDM. Sedentary work was associated with an increased risk of NIDDM with an odds ratio of 3.90 (95% CI 2.30-6.63). Conclusions: Apart from other risk factors, smoking and alcohol consumption are significant lifestyle risk factors for NIDDM in males.